KECERNAAN BAHAN KERING DAN PROTEIN KASAR PAKAN AYAM KAMPUNG BERBAHAN DASAR LUMPUR SAWIT TERFERMENTASI - Djunu, Sri Suryaningsih; Mukhtar, Muhammad; Saleh, Ellen J; Fathan, Suparmin; Taha, siswatiana R (Gorontalo Journal of Equatorial Animals, 2023)
ABSTRACTThis study aims to determine the digestibility of dry matter and crude protein digestibility of balitnak superior village chicken fed non-fermented palm sludge and fermented palm sludge. Using a completely randomized design (CRD) with 5 treatments and 3 replications, consisting of P0: rations without palm sludge, P1: rations + 10% non-fermented palm sludge, P2: rations + 10% fermented palm sludge, P3: rations + 20% sludge non-fermented palm oil, P4: Ration + 20% fermented palm sludge. The study used 15 balitnak superior village chicken aged 8 weeks. Parameters measured included dry matter digestibility and crude protein digestibility. The results showed that the administration of palm sludge had a significant effect (P0.05) on dry matter digestibility, the highest percentage of dry matter digestibility was when using 20% fermented palm sludge (P4: 89.24%). The digestibility value of crude protein had a significant effect (P0.05) with the highest percentage of crude protein digestibility in the ration without palm oil sludge (P0: 21.03%).Keywords: Fermented Palm Sludge; Dry Matter Digestibility; Crude Protein Digestibility; Balitnak Superior Village Chicken